Submarine torpedo tactics : an American history - Monroe-Jones, Edward; Roderick, Shawn S., 1976- (McFarland & Company, Inc., Publishers, 2015)
"The reader travels through World War II and the Cold War as submarines and torpedoes enter the nuclear age. Filled with diagrams and illustrations the narration carries the reader into the attack center as "battle stations torpedo!" resounds through a submarine's compartments"--